2011
DOI: 10.15288/jsad.2011.72.141
|View full text |Cite
|
Sign up to set email alerts
|

Depressive Symptoms, Friend and Partner Relationship Quality, and Posttreatment Abstinence

Abstract: ABSTRACT. Objective: This study employed a prospective design to examine the role of friend and partner relationship quality 1 year following substance use disorder treatment in the association between depressive symptoms at discharge from treatment and abstinence from substance use 2 years after treatment. Method: The sample consisted of 1,453 male veterans who used alcohol and at least one other substance in the 3 months before treatment admission, who completed treatment, and who were abstinent from substan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(3 citation statements)
references
References 60 publications
0
3
0
Order By: Relevance
“…Patients who self-identified as White were coded “0,” and patients of other races and ethnicities were coded “1.” Employment status has also been identified as an important correlate of posttreatment substance use (Melvin, Kock, & Davis, 2012). Patients who reported they were working upon treatment initiation were coded “0” and those who were not working were coded “1.” Evidence has also shown relationship status to be significantly associated with posttreatment substance use (McKee, Bonn-Miller, & Moos, 2011). Patients who were single and reported never having been married were coded “1,” and patients who were in a different type of relationship were coded “0.” Education level has also been identified as an important factor related to responsiveness to substance use treatment (Holtyn, DeFulio, & Silverman, 2015).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Patients who self-identified as White were coded “0,” and patients of other races and ethnicities were coded “1.” Employment status has also been identified as an important correlate of posttreatment substance use (Melvin, Kock, & Davis, 2012). Patients who reported they were working upon treatment initiation were coded “0” and those who were not working were coded “1.” Evidence has also shown relationship status to be significantly associated with posttreatment substance use (McKee, Bonn-Miller, & Moos, 2011). Patients who were single and reported never having been married were coded “1,” and patients who were in a different type of relationship were coded “0.” Education level has also been identified as an important factor related to responsiveness to substance use treatment (Holtyn, DeFulio, & Silverman, 2015).…”
Section: Methodsmentioning
confidence: 99%
“…Patients who reported they were working upon treatment initiation were coded "0" and those who were not working were coded "1." Evidence has also shown relationship status to be significantly associated with posttreatment substance use (McKee, Bonn-Miller, & Moos, 2011). Patients who were single and reported never having been married were coded "1," and patients who were in a different type of relationship were coded "0."…”
Section: Independent Variablesmentioning
confidence: 99%
“…Recently, the impact of relationship quality has been studied among samples of people with comorbid alcohol use and substance use disorders and among individuals with primary drug use disorders. In several treatment studies conducted of patients with alcohol use disorders or comorbid alcohol and drug use disorders, marital quality (or lack of marital stress) has been predictive of better outcomes (McKee, BonnMiller, & Moos, 2011;Tracy, Kelly, & Moos, 2005). In addition, Heinz, Wu, Witkiewitz, Epstein, and Preston (2009) found that a positive relationship with a married partner led to better outcomes among patients with cocaine or heroin use disorders.…”
Section: Salutary Influence Of Marital Quality On Substance Usementioning
confidence: 99%